Characteristic and biosorption capacities of orange peels biosorbents for removal of ammonia and nitrate from contaminated water - S. Dey (Elsevier, 2021)
The ammonia and nitrate are one of the most common groundwater contaminants present in the rural areas. Therefore it is necessary to remove ammonia and nitrate from water. There are several methods aviliable for removal of ammonia and nitrate present in the ground water among these methods the biosorption is a simple, economical and environment-friendly method for removal of ammonia and nitrate from water. Biosorption is a physiochemical process that occurs naturally in certain biomass which allows it to concentrate passively and bind contaminants onto its cellular structure. Every biosorbent had different physical, chemical and biological properties for ammonia and nitrate removal from water. The orange peels biosorbent is one of the best biosorbent for removal of ammonia and nitrate present in water. The orange peels biosorbent concentration of 4gm is highly capable for ammonia and nitrate removal from water. The optimum biosorption of ammonia and nitrate over orange peels biosorbent was obtained at pH = 5.5, contact time = 60 min, temperature = 35 °C and agitation speed = 90 rpm. The characterizations of orange peels biosorbents are done by several techniques like XRD, FTIR, BET and SEM-EDX. These results are interpreted in terms of structure of orange peels active biosorbent. The reusability of orange peels biosorbent was also tested and found that no high level of significant change in its performances even after reuses.